Perancangan Sistem Informasi Inventaris Desa Berbasis Web Studi Kasus: Desa Bukit Subur Merangin - Ichsandi Ichsan; Mai Selvia Ningsih (Hiradika | Hira Institute, 2024)
The inventory management in Bukit Subur Merangin Village is still conducted manually, leading to potential errors and delays in data handling. This study aims to design a web-based inventory information system using the SDLC Waterfall model methodology. The system was developed using PHP programming language, MySQL database, and CSS for interface design. System modeling was performed using Unified Modeling Language (UML). The development stages included requirements analysis, system design, implementation, testing, and maintenance. The results indicate that the designed system improves efficiency and accuracy in village inventory management and facilitates user access through a web-based platform. System testing using the Black Box method showed valid results for all tested features.